2005
DOI: 10.2190/33jh-ktv4-be2w-aw05
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole in the Treatment of Delirium

Abstract: Aripiprazole appears to be effective in reducing the symptoms of delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 7 publications
1
9
0
1
Order By: Relevance
“…Similar responses to quetiapine and amisulpiride were reported in an open randomized prospective study [30]. Aripiprazole has also been reported in case reports [56,57] and a case series [58] to be of benefit in treating delirium.…”
Section: Atypical Antipsychoticssupporting
confidence: 71%
“…Similar responses to quetiapine and amisulpiride were reported in an open randomized prospective study [30]. Aripiprazole has also been reported in case reports [56,57] and a case series [58] to be of benefit in treating delirium.…”
Section: Atypical Antipsychoticssupporting
confidence: 71%
“…Perospirone has been reported to be the fourth AP (after risperidone, quetiapine, haloperidol, and followed by olanzapine and aripiprazole) in a large study of 2453 patients treated for delirium [44]. Aripiprazole, which has D2 and 5-HT1A partial agonist properties, has been successfully used in delirium [66,67], particularly in the hypoactive subtype [68], with a low rate of adverse side effect [69,70]. Amisulpride, also an antipsychotic with atypical properties, showed a comparable efficacy and tolerability with quetiapine in one study [71] and a significant improvement of delirium symptoms in another study of medically ill patients with delirium [72].…”
Section: Antipsychotics (Aps)mentioning
confidence: 99%
“…The authors also reported the case of a 37‐year‐old woman with alcohol‐withdrawal delirium who was treated with 15‐mg aripiprazole. The patients' Mini‐Mental State Examination scores improved (from 5 to 28 and from 7 to 27, respectively) while their Delirium Rating Scale scores decreased (from 28 to 6 and from 18 to 6, respectively) …”
Section: Literature Review Of the Efficacy And Safety Of Aripiprazolementioning
confidence: 97%
“…The patients' Mini-Mental State Examination scores improved (from 5 to 28 and from 7 to 27, respectively) while their Delirium Rating Scale scores decreased (from 28 to 6 and from 18 to 6, respectively). 87,88 Straker et al evaluated the effect of aripiprazole at 5-15 mg/day (average: 8.9 mg/day) for delirium in 14 patients aged 18 to 85 years. A Delirium Rating Scale-Revised-98 improvement of 50% or more was seen in half of the patients by day 5 and in 12 patients by the end of treatment.…”
Section: Literature Review Of the Efficacy And Safety Of Aripiprazolementioning
confidence: 99%